Arbitral awards : grounds for review - Mohammad, Mohammad Tahir Sabit (Current Law Journal, 2020)
Typically, one would presume that judicial review, in the context of arbitration, refers to the process for setting aside an arbitral award under s. 37 of the Malaysian Arbitration Act 2005 (‘Act’). We, however, follow a broader view based on the outcome of judicial scrutiny and substance, i.e. the power of the court whenever it is authorised under the Act to intervene or re-examine the validity of an arbitral award. This may be setting aside the award under s. 37 for domestic arbitration and the recognition and enforcement of foreign arbitral awards under ss. 38-39.2 Naturally, we do not refer to the power of the court under ss. 10 and 11 of the Act or other sections that authorise court action prior to or during the process of arbitration.